2022
DOI: 10.3390/microorganisms11010021
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Competitive ELISA and Western Blot Methods for the Detection of Antibodies against Theileria equi and Babesia caballi

Abstract: Theileria equi (T. equi) and Babesia caballi (B. caballi) are the causative pathogens of Equine piroplasmosis (EP), a disease that has brought huge economic losses and great restrictions to the global equine industry. Rapid and accurate diagnostic methods are critical for the effective monitoring of the disease. In this study, we developed novel competitive ELISA methods and western blot assays based on the EMA1 or Bc48 proteins to detect antibodies against T. equi or B. caballi, respectively. In the novel cEL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…ELISA kits for equine piroplasmosis are available commercially but require multiple steps, including dilution of serum, incubation of primary antibody, and incubation of secondary antibody, as well as washing at each step. Therefore, a competitive ELISA with an improved protocol was developed by introducing a direct HRP conjugation [17]. The coincidence rates between this novel ELISA and the commercial cELISA assays were 97.5% for T. equi and 98% for B. caballi.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…ELISA kits for equine piroplasmosis are available commercially but require multiple steps, including dilution of serum, incubation of primary antibody, and incubation of secondary antibody, as well as washing at each step. Therefore, a competitive ELISA with an improved protocol was developed by introducing a direct HRP conjugation [17]. The coincidence rates between this novel ELISA and the commercial cELISA assays were 97.5% for T. equi and 98% for B. caballi.…”
Section: Discussionmentioning
confidence: 99%
“…Plates were read on a portable microplate reader at an optical density of 450 mm (The Absorbance 96, Byonoy GmbH, Hamburg, Germany). The percentage inhibition equal to or greater than 40% identi ed an antibody-positive sample, and the sample was regarded as antibody-negative below < 40% [17].…”
Section: Competitive Elisamentioning
confidence: 99%
See 2 more Smart Citations
“…This indicated that the host has strong humoral immunity against these proteins. Bc48 is one rhoptry protein of merozoites of B. caballi, which was previously evaluated as a promising antigen for the serological detection of antibodies of B. caballi [12]. Moreover, BC134 protein was developed and proved to be highly specific for the detection of B. caballispecific equine antibodies [13].…”
Section: Introductionmentioning
confidence: 99%